PELATIHAN SOLIDWORKS UNTUK MENDESAIN BENDA KERJA DI DESA WANASARI - Sigit Ugi Maulana; Yopi Handoyo; Setyo Supratno (Universitas Islam 45 Bekasi, 2022)
The world of education is currently facing the industrial revolution 4.0, for the younger generation it is necessary to prepare in terms of abilities in the computer field. Facing the ASEAN Economic Community, competition in the job market is very wide open. The tight world of industrial competition requires workers who are ready to work. Science and technology programs for the community, especially for youth, are intended to help align with the needs of the business world. Training in drawing techniques using computers must be added specifically, one of which is with the necessary development, namely being skilled at using solidwork software. In this case, youth can improve their skills in using software by participating in solidwork training using online methods, namely through zoom, which includes presentation orientation activities, structured exercises and independent exercises. This activity was carried out because considering the demands of the times in the field of design, where designs can be done efficiently with accurate results, repairs can be made in a short time if something goes wrong. This activity is expected to show a positive response from youth in the wanasari village.